Evaluation of a partially de-oiled microalgae product in nursery pig diets. Issue 2 (13th April 2018) - Urriola, Pedro E; Mielke, Joey A; Mao, Qingqing; Hung, Yuan-Tai; Kurtz, John F; Johnston, Lee J; Shurson, Gerald C; Chen, Chi; Saqui-Salces, Milena
Abstract: Although microalgae can be used as a source of energy and macronutrients in pig diets, there is limited information on the use of partially de-oiled microalgae coproducts in swine feeding programs. The objectives of this study were to evaluate the effects of a partially de-oiled microalgae extract (MAE ) in nursery pig diets on growth performance and health status. A total of 300 pigs (initial BW = 6.3 ± 2.1 kg) were used in a 42-d experiment. Treatments included a standard corn-soybean meal control diet, and diets containing 1, 5, 10, or 20% MAE replacing primarily corn. The ME content of MAE was calculated from the chemical composition, and diets were formulated to meet or exceed nutrient requirements for nursery pigs. Pigs were stratified by weaning BW into 12 blocks in a randomized complete block design, with sex distributed evenly among blocks. Pens of pigs (5 pigs/pen) were assigned randomly within block to one of five dietary treatments. Pig BW and feed disappearance were recorded weekly. On day 42, 30 pigs were harvested and sections of the jejunum and ileum were collected for gut morphology analysis, and a liver sample was collected for metabolomic analysis using liquid chromatography-mass spectroscopy. Data were analyzed by ANOVA with diet as treatment effect, and contrasts were used to test linear or quadratic effects of dietary MAE inclusion level. Overall, pigs fed 1% and 5% MAE had the greatest (quadratic P < 0.05) ADG, resulting from greater (quadratic P < 0.05) ADFI. There was a tendency for a greater number of pigs requiring injectable treatments (P = 0.16) and a greater mortality (P = 0.14) in pigs fed the control diet than pigs in any of the diets with the MAE. Final BW increased (P < 0.05) for pigs fed 1% and 5% MAE diets. The improvements in ADG were not explained by differences in mucosa height or goblet cell count among dietary treatments. Pigs fed diets containing 1% or 5% MAE had relatively less concentration (P < 0.05) of ammonia in the liver and had changes in metabolites associated with the urea cycle. In conclusion, feeding MAE resulted in increased growth responses and may have beneficial health effects when fed to nursery pigs.